Mice Overexpressing Both Non-Mutated Human SOD1 and Mutated SOD1G93A Genes: A Competent Experimental Model for Studying Iron Metabolism in Amyotrophic Lateral Sclerosis - Gajowiak, Anna; Styś, Agnieszka; Starzyński, Rafał R.; Bednarz, Aleksandra; Lenartowicz, Małgorzata; Staroń, Robert; Lipiński, Paweł (Frontiers in Molecular Neuroscience, 2016)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by degeneration and loss of motor neurons in the spinal cord, brainstem and motor cortex. Up to 10% of ALS cases are inherited (familial, fALS) and associated with mutations, frequently in the superoxide dismutase 1 (SOD1) gene. Rodent transgenic models of ALS are often used to elucidate a complex pathogenesis of this disease. Of importance, both ALS patients and animals carrying mutated human SOD1 gene show symptoms of oxidative stress and iron metabolism misregulation. The aim of our study was to characterize changes in iron metabolism in one of the most commonly used models of ALS – transgenic mice overexpressing human mutated SOD1G93A gene. We analyzed the expression of iron-related genes in asymptomatic, 2-month old and symptomatic, 4-month old SOD1G93A mice. In parallel, respective age-matched mice overexpressing human non-mutated SOD1 transgene and control mice were analyzed. We demonstrate that the overexpression of both SOD1 and SOD1G93A genes account for a substantial increase in SOD1 protein levels and activity in selected tissues and that not all the changes in iron metabolism genes expression are specific for the overexpression of the mutated form of SOD1.